VISUALIZATION METHODS OF IMAGE CLASSIFICATION PROCESS IN NEURAL NETWORKS - Vogulis, Kaspars; Platonovs, Valdis; Judovičs, Edgars; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The aim of the work was to find and describe ways of visualising layers of neural netwoks, which analyse images and classify them. By visualising network layers, scientists and developers could see features, which influence on results of neural network mapping, training and overall result. In this paper, authors demonstrate different visualization methods, which can be applied by machine learning engineers.